How is vocabulary involved in second language reading comprehension? A study in Chinese-English bilingual children - Qiuzhi Xie; Susanna Siu-Sze Yeung (PLoS ONE, 2025)
It remains unclear as to how vocabulary contributes to reading comprehension in a second language (L2). This study aims to explore the specific roles of vocabulary in reading comprehension in children learning English as an L2 based on three theoretical perspectives. Namely, whether vocabulary should be considered as a subcomponent of language comprehension, an independent predictor of reading comprehension, or an indirect predictor of reading comprehension through decoding and listening comprehension? A total of 167 Grade 4 and 5 Chinese primary school English learners with a mean age of 9.96 years old in Hong Kong participated in this study, and they completed a series of English language tasks. The measurement models indicated that vocabulary was strongly associated with both decoding and listening comprehension, explaining above 65% of their variance. The results of structural equation modeling indicate that vocabulary substantially and indirectly contributed to reading comprehension (accounting for around 44% of its variance) through decoding and language comprehension. Theoretical and practical implications are discussed.